2016
DOI: 10.1063/1.4968876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyurethane (PU) – bioactive glass (BG) ratio on the development of BG reinforced PU scaffold

Abstract: Abstract. Nowadays, variety of biomaterials may be used to produce implanted scaffolds such as metal-based, ceramicbased and polymer-based materials. In this study, porous bioactive glass (BG) reinforced polyurethane (PU) composite scaffolds with different PU:BG mass ratio (10 to 40 wt%) were fabricated as a potential candidate for synthetic bone graft. The PU-BG scaffolds were prepared using solvent casting combined with salt leaching (SCPL) method and were subjected to several characterizations including fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…FTIR spectra showed that the Ag‐NPs addition was not effective on the functional groups in the gelatin nanofiber structure, but BG content had the effect of reducing the density of the functional groups. It can be argued that the reason why the characteristic bands of the BG are not visible is because of the overlapping Gt bands …”
Section: Resultsmentioning
confidence: 99%
“…FTIR spectra showed that the Ag‐NPs addition was not effective on the functional groups in the gelatin nanofiber structure, but BG content had the effect of reducing the density of the functional groups. It can be argued that the reason why the characteristic bands of the BG are not visible is because of the overlapping Gt bands …”
Section: Resultsmentioning
confidence: 99%